Identification of Subsurface Structures in Jaboi Hot Spring Sabang Using Electrical Resistivity Tomography - Darisma, Dian; Idris, Syafrizal; Munir, Badrul; Marwan, Marwan; Salsabila, Rifa Salma (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
The Jaboi geothermal field possesses a capacity of 50 MWe and is set to be developed into a power plant with a configuration of 2x5 MWe. This study seeks to develop a more detailed subsurface model utilizing the two-dimensional electrical resistivity tomography near Jaboi hot spring. This study employs the Wenner-Sclumberger configuration, which effectively characterizes subsurface models in horizontal and vertical dimensions. This method effectively models subsurface conditions by categorizing the resistivity values of rocks into three distinct layers. From line JB1, it can be interpreted as a fluid path, supported by the presence of surface manifestations. It remains uncertain whether a fluid path is present in line JB2. The rock interpretation results at the study site indicate a predominance of tuff mixed with pumice flakes and sandstone and clay tuff combined with agglomerates. The aquifer layer at the study site begins at a depth of 50 m, exhibiting a resistivity value ranging from 2 to 10 Ωm.